PEMBATASAN TERHADAP HAK DAN KEBEBASAN BERAGAMA DI INDONESIA - Muwaffiq Jufri (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2016)
As one of modern law state, Indonesia provides arrangement and guarantee of human rights and freedom of religion. Moreover, this guarantee is clearly stated in the Constitution of the Republic of Indonesia Year 1945. It indicates the existence of human rights and freedom of religion is a constitutional right. Nevertheless, the limitations existed on freedom of religion set out in some legislations affect negatively due to unclear concept of those arrangements. It is became worsen when the limitations of provisions are actually used to justify the action of radicalism in the name of religion. Therefore, scientific studies about the conception of limitations on freedom of religion become urgent as a preventive step in order to avoid the misuse of provisions limitations in the freedom of religion